(untitled) (Stavební obzor - Civil Engineering Journal, 2020)
The types of structures, for construction of which it is expedient to use circular foundations, are considered. The advantages of the circular foundations as compared with other types of foundations are determined. Applying the method of boundary element (MBE), the search of optimal ratio of the internal and external diameters of circular foundation is performed to obtain maximum carrying capacity of tower drier circular foundation. The comparison of the numerical studies with the experimental data is carried out, carrying capacity of tower drier circular foundation in case of rational relations of its internal and external diameters is determined. The technique of non-linear behaviour of the circular foundation under loading as the most economically efficient type of foundation construction for ring in plan buildings is developed.